Analisis Semiotika Roland Barthes Pada Logo HUT ke-23 APEKSI 2023 - Didiek Prasetya; Heri Iswandi; M. Choirul Iqbal (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
The APEKSI 23rd Anniversary logo displayed in the 2023 National Working Meeting (Rakernas XVI) in Palembang City not only serves as a symbol of the visual identity of the activity, but also as a symbolic communication medium that conveys cultural messages, institutional values, and a collaborative spirit between city governments in Indonesia. This research is motivated by the urgency to understand how visual elements in logo design are able to represent local identity while depicting nationalist values in the context of local government visual communication. The purpose of this research is to interpret the visual meaning contained in the logo through Roland Barthes' semiotic approach, which divides the meaning process into three levels: denotative, connotative, and mythological. This research uses a qualitative descriptive method with visual analysis techniques on logo design elements, including the modification of the number